Development of Small Ball Game Learning Through Catch Ball Game to Enhance Motoric and Cognitive Skills In Elementary School Students - Bintoro Widodo; Nurhasan Nurhasan; Suroto Suroto; Rizki Fitri Rahima Uulaa (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to develop a small ball game model (in this case, a catch ball game) to determine students' motor and cognitive skills. The development of this small ball game model also aims to know students' cognition, such as cooperation, problem-solving, discussion, and critical thinking. Method: This study has a qualitative approach, using a checklist observation method to observe motor skills in throwing and catching a ball. In cognitive, students use the results of questionnaires and student interviews. Results: The results obtained from this study on the motor skills of catching the ball were 80% of students with a total of 26 students in categories according to the age level of the development of ball catching skills. 20% fall into the category that needs to follow the age level of the development of ball-catching skills. For motor skills in throwing the ball, 80% of students enter the category according to the age level of the development of skills in throwing the ball. Furthermore, 20% of students in the category need to follow the age level of skills development in throwing the ball. For cognitive students, the catch ball game shows behavior during games such as cooperation, problem-solving, discussion, and critical thinking. Novelty: This research was conducted at PES Rampal Celaket 02 Malang City. The results of this study can also help physical education teachers, especially learning small ball material to improve students and cognitive skills of fourth-grade elementary school students.